Reconsolidation or interference? Aging effects and the reactivation of novel and familiar episodic memories. Issue 7 (8th August 2020) - Howe, Mark L.; Akhtar, Shazia; Bland, Cassandra E.; Hellenthal, Maria V.
ABSTRACT: We examined aging effects in reconsolidation and interference in episodic memory by reactivating memories for well-learned items in young and healthy older adults while controlling memory strength and the degree semantic processes contributed to memory. In Experiment 1, young and old adults learned pairs of real words and images to a strict criterion. After 24-hours, half of the images were reactivated and new words were paired with the images and learned to criterion. Following a 1-week delay, recognition and source monitoring were measured for both sets of pairings. Experiment 2 was a replication of Experiment 1, but using previously unknown novel words and unusual images. As predicted, older adults needed more trials to learn both the A-B and A-C pairings. Older adults required more trials to learn the new associations for reactivated than the not reactivated pairs, although there was no main effect of reactivation and no Age x Reactivation interaction for measures of recognition one-week later. These results are inconsistent with previous findings concerning age differences in reactivation effects in episodic memory. Instead, they suggest that once memory strength and input from semantic memory are better controlled, young and old adults perform similarly on tests of long-term recognition memory.